2008
DOI: 10.1016/j.ajog.2008.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and adverse birth outcomes: a study from Pakistan

Abstract: OBJECTIVES-Periodontal disease may increase the risk of adverse birth outcomes; however, results have been mixed. Few studies have examined periodontal disease in developing countries. We describe the relationship between periodontal disease and birth outcomes in a community setting in Pakistan. METHODS-Enrollment occurred at 20-26 wks.A study dentist performed the periodontal examination to assess probing depth (PD), clinical attachment level (CAL), gingivitis index (GI) and plaque index (PI). Outcomes includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 31 publications
1
50
0
1
Order By: Relevance
“…In a prospective cohort study in Pakistan, 1152 women were assessed for dental status and followed for pregnancy outcomes. 17 Low birth weight was not related to measures of periodontal disease but stillbirth and neonatal and perinatal deaths increased with severity of periodontal disease. In a study of 1404 pregnant women in Spain, Lopez 18 reported a modest association between periodontitis and preterm birth.…”
mentioning
confidence: 95%
“…In a prospective cohort study in Pakistan, 1152 women were assessed for dental status and followed for pregnancy outcomes. 17 Low birth weight was not related to measures of periodontal disease but stillbirth and neonatal and perinatal deaths increased with severity of periodontal disease. In a study of 1404 pregnant women in Spain, Lopez 18 reported a modest association between periodontitis and preterm birth.…”
mentioning
confidence: 95%
“…On the other hand, some studies have showing a modest association between PD and adverse pregnancy outcomes [9], or no association at all. [10-12].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies within living populations have shown significant associations between periodontal disease and other diseases, such as cardiovascular diseases, respiratory infections, cancer (e.g., lung, kidney, pancreatic, oral, esophageal, upper gastrointestinal, gastric, and kidney cancers), Alzheimer's disease, obesity, diabetes, renal disease, osteoporosis, and rheumatoid arthritis (for example, see the following reviews: Hollister and Weintraub, 1993;Li et al, 2000;Kowolik et al, 2001;Slots, 2004;Pihlstrom et al, 2005;Johnson et al, 2006;Irwin et al, 2008;Williams et al, 2008). Periodontal disease is also associated with increased risks of spontaneous preterm birth, preeclampsia, low birth weight, and stillbirth (Holmstrup et al, 2003;Goepfert et al, 2004;Boggess, 2005;Boggess et al, 2006;Mobeen et al, 2008;Ruma et al, 2008;Polyzos et al, 2009).…”
mentioning
confidence: 99%